Yield and Fruits Quality of Potted-Strawberry Grown with Bacillus-Coated NPK Fertilizer - Hindersah, Reginawanti; Fitriatin, Betty Natalie; Setiawati, Mieke Rochimi; Suryatmana, Pujawati; Risanti, Rara Rahmatika; Aditya, Fasa; Nugraha, Gita Bina (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2025)
NPK fertilizer coated with rhizobacteria Bacillus supports biofertilizer use while reducing the dose of NPK fertilizer. The objective of the greenhouse experiment was to analyze the growth and fruit production of potted strawberries following Bacillus-coated NPK 16-16-16 (BCN). The research was set up in a Completely Randomized Block Design that tested four BCN dosage and type combinations. The control treatment consisted of no fertilizer and complete and a half dosage of NPK fertilizer 16-16-16. The results showed that the shoot height and the fruit number of strawberry cv Festival were not affected by NBB application, but the type of NPK fertilizer affected the fruit weight per plant and sweetness. A complete dosage of BNN formula C produced the most significant fruit weight, but the highest sweetness was obtained from plants treated with half the dose of NPK conventional fertilizer. However, one or half doses of NBB formula G reduced the fruit sweetness. This experiment shows the potential of NBB to support strawberry production in a greenhouse, but a longer duration of the experiment is needed to obtain more harvest data.